2011
DOI: 10.1007/s10482-011-9563-4
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of the S-layer protein from the probiotic strain Lactobacillus helveticus M92

Abstract: The objective of this study was the characterisation of the S-layer protein (SlpA) and its functional role in the probiotic activity of Lactobacillus helveticus M92. SlpA was isolated and identified by SDS-PAGE LC-MS/MS analysis. The slpA gene encoding the SlpA from L. helveticus M92 was sequenced and compared with other well characterised slpA genes. Sequence similarity searches revealed high homology with the SlpA of Lactobacillus strains. Purified SlpA showed significantly better immunomodulatory effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 33 publications
1
54
1
3
Order By: Relevance
“…For instance, it was shown that the Slayer protein from L. acidophilus ATCC 4356 T reduced Salmonella enterica serovar Typhimurium FP1-induced apoptosis in Caco-2 cells, and this effect was dependent on the inhibition of caspase-3 activation (41). In another study, the oral immunization of mice with the purified SlpA from L. helveticus M92 induced an increase in total levels of serum IgG, IgM, and IgA (42).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, it was shown that the Slayer protein from L. acidophilus ATCC 4356 T reduced Salmonella enterica serovar Typhimurium FP1-induced apoptosis in Caco-2 cells, and this effect was dependent on the inhibition of caspase-3 activation (41). In another study, the oral immunization of mice with the purified SlpA from L. helveticus M92 induced an increase in total levels of serum IgG, IgM, and IgA (42).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the involvement of SLP in this process has been particularly studied for bacterial strains with potentiality as probiotics. In fact, the removal of SLP with 5 M LiCl reduces the autoaggregation ability of different lactobacilli such as Lactobacillus acidophilus ATCC 4356 (Kos et al 2003), L. kefiri CIDCA 8321 (Garrote et al 2004) and L. helveticus M92 (Beganović et al 2011). However, the strong autoaggregating phenotype of L. crispatus ZJ001 could be related to other cell surface components than SLP, since it is not markedly affected by treatment with LiCl (Chen et al 2007).…”
Section: Autoaggregation and Coaggregation With Other Microorganismsmentioning
confidence: 99%
“…A similarity search using the deduced amino acid sequence of the L. helveticus MIMLh5 S-layer protein (EMBL database accession number HE993893) employing the algorithm BLASTP (33) revealed a high level of sequence homology to the other L. helveticus S-layer proteins (11) and to L. acidophilus S-layer proteins (8,24) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been documented that immunomodulatory properties of Lactobacillus spp. (e.g., Lactobacillus acidophilus NCFN [8,9], Lactobacillus brevis ATCC 8287 [10], and L. helveticus strain M92 [11]) are due to their surface layer (S-layer) protein. Recently it was demonstrated that the immunostimulatory properties of L. helveticus MIMLh5 are mainly mediated by its S-layer protein as well (12).…”
mentioning
confidence: 99%